2021
DOI: 10.1371/journal.pone.0248701
|View full text |Cite
|
Sign up to set email alerts
|

MRI risk factors for development of avascular necrosis after closed reduction of developmental dysplasia of the hip: Predictive value of contrast-enhanced MRI

Abstract: Purpose The purpose of this study was to identify imaging risk factors on contrast-enhanced hip MRI after closed reduction of developmental dysplasia of the hip (DDH) that could predict future development of avascular necrosis (AVN) of the femoral head. Materials and methods Fifty-eight infants (F: M = 53: 5, aged 3–18 months) who underwent immediate postoperative contrast-enhanced hip MRI after closed reduction of DDH were included in this study. Quality of reduction (concentric vs eccentric reduction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…First, this study was a single-center retrospective study, which had a relatively poor sample representation and limited patient data. Global decreased enhancement of the femoral head, redislocation, and surgical treatment without femoral shaft shortening were found to be risk factors for postoperative ANFH ( 25 27 ). Since the retrospective nature of this study, some data cannot be obtained at present, and more factors need to be evaluated in the future.…”
Section: Discussionmentioning
confidence: 98%
“…First, this study was a single-center retrospective study, which had a relatively poor sample representation and limited patient data. Global decreased enhancement of the femoral head, redislocation, and surgical treatment without femoral shaft shortening were found to be risk factors for postoperative ANFH ( 25 27 ). Since the retrospective nature of this study, some data cannot be obtained at present, and more factors need to be evaluated in the future.…”
Section: Discussionmentioning
confidence: 98%
“…Given its less invasive nature, closed reduction is generally preferred to open reduction whenever possible [26]. However, treatment with closed reduction has been associated with adverse outcomes including AVN of the femoral head and insufficient long-term reduction of the hip requiring a second revision procedure [15][16][17][18]. It remains unclear which patients are most at risk of experiencing these complications and which would benefit the most from this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported success rates ranging from 54.5% to 95.7% in patients treated with closed reduction [1,[8][9][10][11][12][13][14]. Despite these high success rates, the procedure has also been associated with complications including avascular necrosis (AVN) and failure of long-term maintenance of reduction requiring secondary reconstructive procedures [15][16][17][18]. Currently, there is variability in the literature that describes the rates of these complications following treatment with closed reduction and factors associated with these complications.…”
Section: Introductionmentioning
confidence: 99%
“…또한, 수술 전후 대퇴골두의 동심성 정복을 제한하는 장애물을 평가할 수 있는데, 비대해진 섬유지방 조직(pulvinar) 또는 비구 내로 뒤집힌 관절순(labrum) 등이 대퇴골두와 비구 사이에 끼어 있는지 등을 평가한다( Fig. 4B ) ( 7 ). 고관절 석고 고정(hip spica cast)이 적용된 상태에서는 일반적인 고관절 초음파 검사 방법 대신, 전방 고관절 초음파 검사(van Douveren’s method)를 이용해 대퇴골두의 정복 여부를 평가할 수 있으며, 투과도 확보를 위해 저주파수 볼록 트랜스듀서를 사용할 수 있고 해상도 손실은 불가피하지만 쉽게 검사할 수 있다는 장점이 있다( Fig.…”
Section: 선천성 발달성 고관절 질환unclassified